Strategi Penguatan SDM dan Pemasaran Digital Bagi Pelaku UMKM di Kota Bengkulu - Ade Tiara Yulinda; Kusuma, Merta; Arianto, Tezar; Yuniarti, Rina (Universitas Malikussaleh, 2025)
The growth of Micro, Small, and Medium Enterprises (MSMEs) in Bengkulu City has shown a positive trend in recent years. However, this progress has not been fully accompanied by increasing the capacity of human resources (HR) and the optimal use of digital technology. In the era of the digital economy marked by accelerated technology adoption and changes in consumer behavior, MSME actors are required to improve competence and adopt adaptive marketing strategies. The community service program initiated by the Faculty of Economics and Business, University of Muhammadiyah Bengkulu aims to strengthen the capacity of human resources and digital marketing skills for MSME actors in Bengkulu City. The activity is carried out through an educational, participatory, and needs-based approach, which includes digital literacy training, business management, and the use of social media and e-commerce platforms. The results of the program implementation show an increase in understanding of the importance of digitalization and practical skills in modern and market-oriented business management. Strengthening human resources and implementing a targeted digital marketing strategy is expected to increase competitiveness, expand market reach, and encourage sustainable adaptation in facing digital economy challenges. This kind of intervention needs to be carried out in a sustainable and collaborative manner to support an inclusive and resilient local MSME ecosystem.